(untitled) (Revista Latino-Americana de Enfermagem, 2019)
Objective: To evaluate the effectiveness of an educational workshop using games to improve self-monitoring of blood glucose techniques for school children with type 1 diabetes. Method: A quasi-experimental study was conducted with school children who attended two outpatient clinics of a university hospital. Data were collected by systematic observation of the self-monitoring of blood glucose (SMBG) technique before and after the intervention. Data analysis consisted of verifying changes while performing the technique, using pre- and post-intervention compliance rates using statistical tests. The sample consisted of 33 children. Each child participated in one session; 17 educational workshops were conducted in total. Results: We found an increased frequency of SMBG, changing lancets, rotation of puncture sites, as well as calibration and periodic checking of date and time of the glucose meter. Comparisons pre- and post-intervention showed that the average number of steps in accordance with the SMBG technique increased from 5.30 to 6.58, whereas the steps “Changing the lancet of the lancing device”, “Pressing the puncture site” and “Disposing of materials used in a needlestick container” showed statistically significant differences. Conclusion: The educational workshop was effective, as it improved children’s performance of the SBMG technique.